ANALISIS KADAR PENGAWET NATRIUM BENZOAT PADA PRODUK MINUMAN BERKARBONASI DENGAN METODE HPLC - Rahmawati, Rahmawati; Kosman, Rachmat; Effendi, Nurmaya; Ismayani, Nur (Fakultas Farmasi UMI, 2014)
It has been worked a research about the analysis of sodium benzoate content of carbonated beverages which is in Makassar market using High Performance Liquid Chromatography (HPLC) reverse phase. In this research, the analysis was conducted on four brands of carbonated beverages products. The results of analysis are sample A contains 47,6907 mg/kg, sample B 152,9348 mg/kg, sample C 271,4082 mg/kg, and sample D 357,3797 mg/kg of sodium benzoate. The four samples appropriate Permenkes No. 722/Menkes/Per/IX/1988 are <600 mg/kg. Key words : Natrium Benzoate, HPLC, Carbonated Beverages